2008
DOI: 10.1242/jcs.014076
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fyn function in hemostasis and αIIbβ3-integrin signaling

Abstract: Recent studies have shown that Src-family kinases (SFKs) play an important role in mediating integrin signalling, and the β3 subunit of αIIbβ3 integrin has been shown to interact with multiple SFK members. Here, we analyzed the interactions and functional consequences of Fyn and Src binding to αIIbβ3. Fyn associated with the β3 subunit in resting and thrombin-aggregated platelets, whereas interaction between Src and αIIbβ3 was seen predominantly in resting but not in thrombin-aggregated platelets. We have also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 54 publications
5
61
1
1
Order By: Relevance
“…In HeLa cells, Fyn-mRFP was present throughout the plasma membrane, and was apparently enriched in focal adhesions (Reddy et al, 2008). TIR microscopy revealed that Fyn-mRFP had a more uniform distribution than flotillin-1-GFP, and was visibly concentrated in less than 5% of flotillin microdomains (Fig.…”
Section: Et Al 2001mentioning
confidence: 93%
“…In HeLa cells, Fyn-mRFP was present throughout the plasma membrane, and was apparently enriched in focal adhesions (Reddy et al, 2008). TIR microscopy revealed that Fyn-mRFP had a more uniform distribution than flotillin-1-GFP, and was visibly concentrated in less than 5% of flotillin microdomains (Fig.…”
Section: Et Al 2001mentioning
confidence: 93%
“…SFKs can bind directly to β-integrin tails in a tail-and SFK-specific manner, and this interaction contributes to activation of kinase activity and controls cell spreading (Arias-Salgado et al, 2003;Reddy et al, 2008). SFKs also bind to and phosphorylate FAK and FAK-binding proteins.…”
Section: Src-family Kinasesmentioning
confidence: 99%
“…62 Loss of the Src binding site is thought to be calpain-mediated. 63 Fyn-deficient mouse platelets exhibit a less severe spreading defect on fibrinogen compared with Srcdeficient platelets, demonstrating the dominant role of Src downstream of aIIbb3.…”
Section: 51mentioning
confidence: 99%